2014
DOI: 10.17146/aij.2014.274
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Urea Molasses Multi-Nutrient and Medicated Block for Beef Cattle, Beef and Dairy Cow

Abstract: Urea molasses multi-nutrient block (UMMB) is a feed supplement and one of the best formulas constructed by the National Nuclear Energy Agency (BATAN). This supplement contains soya bean meal (SBM) and has been developed using different protein sources, such as Enterolobium cyclocarpum (Ec), soya bean waste sauce (SBWs), wheat pollard (WP) and WP bypass protein (WPBp). It has also been developed using medicated block (MB). The objective is to introduce the P-32 tracer for obtaining a new feed supplement, to app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 2 publications
1
3
0
3
Order By: Relevance
“…A similar response to UMMB supplementation also occurred on the increase of daily live weight gain of Ongole, Simmental, and Fries Holstein (FH) Cross Breed. The increase of daily live weight gain was higher with than without supplement [9]. Similar effects were observed in other ruminant species, such as ewes, sheep and Buffalo [10,11,12].…”
Section: Resultssupporting
confidence: 75%
“…A similar response to UMMB supplementation also occurred on the increase of daily live weight gain of Ongole, Simmental, and Fries Holstein (FH) Cross Breed. The increase of daily live weight gain was higher with than without supplement [9]. Similar effects were observed in other ruminant species, such as ewes, sheep and Buffalo [10,11,12].…”
Section: Resultssupporting
confidence: 75%
“…During this period, the trend still increase in all treatments group but eventually, parasite infestation were significantly higher (p<0.05) in control group as compared to the supplemented group which is at 4083±861 epg. The effect was observed to be more severe at high humidity, especially during rainy reason (Suharyono et al 2014) as faced by the animals from day 45 onwards. In rainy season, there were rapid development of larvae which only takes less than 2 weeks (Harwood 2006).…”
Section: Resultsmentioning
confidence: 92%
“…It was found that basal feeds contain about 15% CP which meet the requirement for dairy goats (Rashid, 2008). Dry matters of UMMB and MUMB were >85% which are sufficient to prevent mould growth (Suharyono et al, 2014). Ash contents in UMMB and MUMB were 17% indicating the presence of mineral premix and salt.…”
Section: Chemical Composition Of Basal Diets and Supplementsmentioning
confidence: 97%